High Prevalence of Dysgraphia in Elementary Through High School Students With ADHD and Autism. Issue 8 (June 2019) - Mayes, Susan D.; Breaux, Rosanna P.; Calhoun, Susan L.; Frye, Sara S.
Objective: Prevalence of dysgraphia by age across all grade levels was determined in students with ADHD or autism.Method: Referred children with normal intelligence and ADHD–Combined, ADHD–Inattentive, or autism ( N = 1, 034) were administered the Developmental Test of Visual-Motor Integration (VMI) and Wechsler Intelligence Scale for Children (WISC).Results: VMI and WISC Coding scores were significantly lower than IQ and the normal mean of 100 for all diagnoses. More than half (59%) had dysgraphia, and 92% had a weakness in graphomotor ability relative to other abilities. Dysgraphia prevalence did not differ between diagnostic or age groups (6-7 years, 56%; 8-10 years, 60%; and 11-16 years, 61%).Conclusion: Dysgraphia is common at all ages in children and adolescents with ADHD and autism. Accommodations and strategies for addressing this problem are discussed.